Measurement Invariance of Internalizing and Externalizing Behavioral Syndrome Factors in a Non-Western Sample. (October 2013) - Yarnell, Lisa M.; Sargeant, Marsha N.; Prescott, Carol A.; Tilley, Jacqueline L.; Farver, Jo Ann M.; Mednick, Sarnoff A.; Venables, Peter H.; Raine, Adrian; Luczak, Susan E.
This study examined the measurement structure of Child Behavior Checklist internalizing and externalizing syndrome scales in 1, 146 eleven-year-old children from a birth cohort in Mauritius. We tested for measurement invariance at configural, metric, and scalar levels by gender and religioethnicity (Creole, Hindu, Muslim). A pared-down model representing five primary factors and two secondary factors met all three forms of invariance, supporting the validity of their use for group comparisons among Mauritian children. As rated by their parents, girls were higher than boys on Somatic Complaints and lower on Aggressive Behavior, Attention Problems, and Externalizing. Creoles were higher than Muslims and Hindus on all seven factors. Hindus were higher than Muslims on Somatic Complaints and lower on Aggressive Behavior. To our knowledge, this is the first study to demonstrate strict invariance of a Child Behavior Checklist-based internalizing and externalizing factor structure among subgroups within a society.